Rights, Welfare, and Mill's Moral Theory. - Lyons, David (Oxford University Press, 1994)
This volume collects David Lyons's essays on Mill's moral theory and includes an introduction which relates the essays to prior and subsequent philosophical developments. The essays defend the beneficiary theory of rights and develop new interpretations of Mill's moral thought.